Relationship between technical knowledge on termite (Coptotermes sp.) at rubber plantation and it’s control method among farmers in Segamat, Johor: case study / Rabialtualadaviah Nasir - Nasir, Rabialtualadaviah (Faculty of Plantation and Agrotechnology, 2017)
Termite is one of pest in rubber plantation. It will cause damage at the base of rubber tree and at the same time it will reduce the latex production. This study was conducted to determine the level of technical knowledge about termite and the pest management practice among farmer in Segamat, on 63 respondents. The background of study was refer to the gender, age, income per month, area of field, experience of pesticide handling, and education level. Most of the farmers were male that range of age 51 years old and above. Most of farmers have below than 10 years of insecticide knowledge. Based on the results, there are significance relationship between the technical knowledge and the control method. It shows the culture control have significances relationship with the technical knowledge among farmers. Moreover, the technical knowledge also has significance relationship between the chemical controls. In conclusion, the technical knowledge among farmers influence the application of control method in the field. The results indicated that most farmers in this district need more education program regarding the insecticide management at the field.